Notes on the Narratological Approach to Board Games - Mattia Thibault (KOME: An International Journal of Pure Communication Inquiry)
Nowadays game studies are in the foreground of cultural and communication debates. Even if video games are strongly studied in semiotics, play is a wide field of study with many areas still unexplored. The area that this paper aims to explore concerns board games and it focuses on the relationship between game and narration and the role of a game’s intertextual dimension from a semiotic point of view. Semiotic tools that have been used include the Greimasian narrative sequence (a structuralist point of view that fits very well with the rigid, explicit grammaticalization of board games) and Génette's narratology, unavoidable for every reflection on intertextuality. Last, but not least, cultural semiotics, based on Jurij Lotman's works, offers a valuable asset for understanding the enveloping and organic structure that surrounds games. The research proceeds to focus on some case studies of three ancient board games - chess, backgammon, and mancalas - underlining their common traits and differences. The paper shows that the structure of board games is very similar to the structure of the Greimasian narrative sequence, but they rather form a hybrid narration in which the player has a primary importance. Moreover, we see that games constantly retrieve sense from different kinds of other texts depending on the culture and society in which the game is played. The aim of this research is not to propound a complete theory, but rather to indicate a possible path to follow, between many, that could be a valuable resource in the exploration and the understanding of play.